Initial Reports of the Deep Sea Drilling Project 1973
DOI: 10.2973/dsdp.proc.18.114.1973
|View full text |Cite
|
Sign up to set email alerts
|

Neogene Foraminifera from the Northeastern Pacific Ocean, Leg 18, Deep Sea Drilling Project

Abstract: Introduction General Methods and procedures Site 172 Geologic and stratigraphic setting Planktonic foraminifera and age Benthonic foraminifera Origin of lower Oligocene carbonate ooze Site 173 Geologic and stratigraphic setting Abundance and preservation of foraminifera Planktonic foraminifera Age, biostratigraphy, and paleo-oceanography Benthonic foraminifera and paleobathymetry Site 174 Geologic and stratigraphic setting Abundance and preservation of foraminifera Planktonic foraminifera, age, and paleo-ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 25 publications
3
45
0
Order By: Relevance
“…Figure 7 shows that most species have rather extended ranges. Comparable results are given for the Pacific by Douglas (1973), Ingle (1973), and Parker (1964).…”
Section: Biostratigraphymentioning
confidence: 48%
See 2 more Smart Citations
“…Figure 7 shows that most species have rather extended ranges. Comparable results are given for the Pacific by Douglas (1973), Ingle (1973), and Parker (1964).…”
Section: Biostratigraphymentioning
confidence: 48%
“…In general, the species composition of the Neogene benthonic population is similar to that described by Cushman (1929) from the oceanic Miocene of Venezuela and Trinidad. Most of the Neogene species recorded by Douglas (1973) and Ingle (1973) from lower middle bathyal depths of the northern Pacific are also present at Site 369. This wide interocean distribution of bathyal Neogene foraminifera should stimulate future correlation studies with benthonic foraminifera.…”
Section: Fluctuation Trends Andmentioning
confidence: 95%
See 1 more Smart Citation
“…This zonation is discussed by Hedgepeth (1957) and Ingle (1973). Unfortunately, the Mediterranean Sea is topographically and hydrographically unlike the open ocean basins of the world.…”
Section: Benthic Foraminifersmentioning
confidence: 99%
“…Several recent studies (Kent et al, 1971;Hays et al, 1969;Ingle, 1973) of Pleistocene climatic events in the North Pacific have found substantial evidence of a major climatic cooling beginning about 700,000 2 years B.P. which is now recognized as the initiation of the so-called glacial Pleistocene.…”
Section: Discussionmentioning
confidence: 99%